Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Perusahaan Telekomunikasi di Indonesia - Joni Hendra; Nurisa Nurisa; Sofie Fadma Sari; Suci Nirwani (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The telecommunications industry in Indonesia plays a vital role in supporting digital transformation and national economic growth. With the increasing demand for communication and data services, telecommunications companies face challenges in maintaining optimal financial performance. This study aims to analyze the financial performance of telecommunications companies in Indonesia through financial ratio analysis. The method used is library research, by reviewing literature related to financial ratios, including liquidity, solvency, activity, and profitability ratios. This analysis seeks to identify the financial strengths and weaknesses of the companies across various aspects. The results show that financial ratios can provide a comprehensive overview of a company's financial condition, including its ability to meet short-term obligations, manage debt, and generate profits. These findings have important implications for company management in making strategic decisions, as well as for investors aiming to evaluate the financial performance of telecommunications companies. It is expected that the results of this analysis will serve as a basis for improving financial efficiency and enhancing the competitiveness of companies amid the evolving dynamics of the telecommunications industry.